PENINGKATAN KESADARAN HUKUM PELAKU USAHA TERHADAP SERTIFIKASI HALAL DALAM MENJAMIN HAK KONSUMEN MUSLIM (Studi Kasus Pelaku Usaha Rumah Makan di Batu Merah Kota Ambon) - Tuti Haryanti (TAHKIM, 2017)
In the era Globalization consumers are too spoiled by businesses by offering a variety of food, where food or drink is possible to be produced quickly by using a device or tool that is sophisticated, eventually consumers off guard in consuming the products offered in the market although it is not in accordance with the provisions of the Shari'a Islam. The current reality, that the issue of certification of halal food has not been a concern for the perpetrators of the restaurant business in Batu Merah city of Ambon, but the government has responded to consumer concerns by enacting several laws and regulations. But the existence of the regulation is not immediately received, obeyed and implemented by businesses. This type of research used in this study is qualitative. The data used in this study are primary data and secondary data. Overall the data obtained and analyzed qualitatively. The results showed that based on legal awareness indicators show that business house eating Red Stone did not know and understand the rules associated with halal certification. Besides the meaning of halal haram perspective of businesses have experienced a reduction of meaning. Lack of knowledge and understanding of the law implies an attitude/behavior of businesses that tend to not comply with the legislation. Therefore, the legal awareness of entrepreneurs against the Red Stone house eating halal certification is still considered very low. Efforts to raise the legal awareness through the dissemination of business principals of law, religious lectures. Key words: legal awareness, business communities, halal certification